Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Anggota Dalam Menabung di KSPPS Khairu Ummah Cabang Puraseda Bogor - Faisal Salistia; Lusi Mariana; Sukarna Sukarna (MES Management Journal, 2023)
The purpose of this study was to determine whether the variables of Service Quality and Product Quality had an effect on customer satisfaction in saving at KSPPS Khairu Ummah, Puraseda Branch. This study uses quantitative methods because it aims to confirm the data obtained in the field with existing theories. The sample was obtained as many as 97 respondents from KSPPS Khairu Ummah Branch Puraseda. Using random sampling technique. While for the technique of data collection is done by using a questionnaire, literature study, interviews, documentation and observation. The data were processed using reliability, validity, classical assumptions, regression equations, statistics and coefficients of determination. From the results of data processing, it shows that Service Quality has a significant effect on the Customer Satisfaction variable which is shown. In the calculation of the hypothesis test with the t-test, partially between service quality and member satisfaction, the tcount value is 4.883 with a ttable value of 1.985, so the hypothesis H0 is rejected. Meanwhile, for the calculation of the t-test between product quality and member satisfaction, the tcount value is 3.859 with a t-table value of 1.985 so that the hypothesis H0 is rejected. So it can be concluded that there is a significant influence between product quality and member satisfaction. From the results of hypothesis testing, it can also be seen that Fcount 72.300 > Ftable 3.097 means that H0 is rejected, so it can be concluded that service quality and product quality simultaneously affect member satisfaction. For R2 of 0.606. So that the ability of the service quality and product quality variables to explain member satisfaction simultaneously is 60.6% influenced and explained while the remaining 39.4% is influenced and explained by other variables not examined. Keywords: Service Quality, Product Quality and Member Satisfaction